Mitochondrial DNA mutations may not be frequent in patients with polycystic ovary syndrome. (August 2013) - Chen, Ruixiang; Wang, Huiling; Li, Shaoping; Ren, Yanfang
<x xml:space="preserve">Abstract</x>